2016
DOI: 10.1134/s10704272160030228
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis and fluorescence study of the grafted salicylidene Schiff base onto SBA-15 mesoporous silica for detecting Zn2+ traces in aqueous medium

Abstract: A selective fl uorescent chemosensor was prepared by anchoring pyridine-2-carbaldehyde Schiff base ligand onto mesochannels of organically modifi ed SBA-15 mesoporous silica. The resulting organic-inorganic hybrid mesoporous chemosensor was characterized by X-ray diffraction, Fourier transform IR spectroscopy, transmission electron microscopy, UV-visible diffuse refl ectance spectra, and photoluminescence spectra. All the results support the idea that successive attachment of the ligand moiety onto one-pot-mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This could help to have the detection limit of 1.6××10 −9 M for the fluoride ions . In another study, Schiff base complex was immobilized over salicylidene functionalized SBA‐15 materials which were later employed as fluorescent chemosensors and showed a great promise for the selective detection of even a trace amount of Zn ions . In another report, Karimi et al .…”
Section: Synthesis Of Organo‐functionalized Molecular Sievesmentioning
confidence: 99%
“…This could help to have the detection limit of 1.6××10 −9 M for the fluoride ions . In another study, Schiff base complex was immobilized over salicylidene functionalized SBA‐15 materials which were later employed as fluorescent chemosensors and showed a great promise for the selective detection of even a trace amount of Zn ions . In another report, Karimi et al .…”
Section: Synthesis Of Organo‐functionalized Molecular Sievesmentioning
confidence: 99%
“…Moreover, for chemosensor applications [27][28][29][30][31][32][33], the regularly arranged pores in its SBA-15 mesostructure can enhance the selectivity to particular guests like organic substance and/ or metal ions [34]. For Schiff base ligands as fluorescent chemosensors in the hybrid mesoporous silica materials, several reports have been published for sensing Al 3+ [35], Hg 2+ [36], Pb 2+ [37], Zn 2+ [38][39][40], and Cu 2+ ions [41][42][43]. In particular, Wang et al [44] and Afshani et al [45] have reported that the grafting of bis-Schiff base N,N′-(1,4-phenylenedimethyli-dyne)bis(1,4-benzenediamine) (PMBA) and salicylaldehyde with SBA-15 can be used for sensing Fe 3+ at a less intense blue-emission peak of the binding site consisting of a broad peak.…”
Section: Introductionmentioning
confidence: 99%